IMPROVING QUICK READING ABILITY STUDENTS USING HORIZONTAL PATTERN SKIPPING TECHNIQUES CLASS X SMA 16 MAKASSAR - Zaenal Zaenal; Muliadi Muliadi; Kasma F Amin (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The purpose of this study was to describe the learning process and improve speed reading skills by using the horizontal pattern skipping technique of class X SMAN 16 Makassar. The subject of this research is class X with 35 students, the type of research used is classroom action research, the data collection method in this study uses test techniques, observation sheets and documentation, data analysis techniques used in this study are qualitative and quantitative techniques. Before the action was given, a pretest was held to determine the students' initial ability to read quickly in the pre-cycle. The results showed that in class X the average score produced in the pre-cycle was 46.3. Then, the communicative method was carried out in cycle 1, so that the results increased by 57.37. After the second cycle of action, the results again increased by 85.57. Based on the results of research and discussion, it can be concluded that there is an increase in the speed reading ability of class X IPS 1 SMAN 16 Makassar students who use the horizontal pattern Skipping technique.